2016
DOI: 10.2147/btt.s87396
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome – a promising anti-cancer target

Abstract: The centrosome, an organelle discovered >100 years ago, is the main microtubule-organizing center in mammalian organisms. The centrosome is composed of a pair of centrioles surrounded by the pericentriolar material (PMC) and plays a major role in the regulation of cell cycle transitions (G1-S, G2-M, and metaphase-anaphase), ensuring the normality of cell division. Hundreds of proteins found in the centrosome exert a variety of roles, including microtubule dynamics, nucleation, and kinetochore–microtubule attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 125 publications
1
26
0
Order By: Relevance
“…Our main goal was to test whether genetic variation confers increased risk for the development of cancer predisposing phenotypes post exposure to HZE radiation. We chose to study centrosome aberrations as our surrogate end point of cancer risk, as it has been well documented that aberrations in centrosome number can disrupt tissue architecture and genomic instability; the two main hallmarks of carcinogenesis (Nigg, 2006;Rivera-Rivera & Saavedra, 2016). We and others have also shown that centrosome defects increase with simple and complex damage (Sato et al, 1983;Sudo et al, 2008, Sridharan et al, 2017 and can sensitively differentiate between radiation and age dependent effects (Sridharan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our main goal was to test whether genetic variation confers increased risk for the development of cancer predisposing phenotypes post exposure to HZE radiation. We chose to study centrosome aberrations as our surrogate end point of cancer risk, as it has been well documented that aberrations in centrosome number can disrupt tissue architecture and genomic instability; the two main hallmarks of carcinogenesis (Nigg, 2006;Rivera-Rivera & Saavedra, 2016). We and others have also shown that centrosome defects increase with simple and complex damage (Sato et al, 1983;Sudo et al, 2008, Sridharan et al, 2017 and can sensitively differentiate between radiation and age dependent effects (Sridharan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the numerous mechanisms attributed to chromosomal instability, several approaches have been proposed to target chromosome instability in cancer. One approach is to target centrosome-associated proteins that regulate microtubule dynamics and the SAC to prevent centrosome amplification, thus preventing chromosome instability [ 87 , 189 , 190 ] . The Cdk4/Cdk6 inhibitor Palbociclib (PD-0332991) in combination with the aromatase inhibitor letrozole has greatly improved the outcomes of ER + , Her2 − advanced breast cancer patients [ 191 , 192 ] .…”
Section: Inhibitors Of Chromosome Instability In Cancer Treatmentmentioning
confidence: 99%
“…In fact, Palbociclib is ineffective in basal breast cancer cells (the subtype with a higher degree of chromosome instability), and patients are harboring alterations in the Rb/E2F pathway [ 193 , 194 ] . Nevertheless, several inhibitors targeting polo-like kinases (Plks) and Aurora kinases (AURKs) have been tested in pre-clinical and clinical trials with mixed outcomes, and this has been extensively discussed elsewhere [ 189 ] . Notably, the inhibitor MLN8237 (Asertib) that targets AURKs exhibited efficacy for several solid tumors and T-cell lymphoma, but not acute myeloid leukemia [ 195 , 196 ] .…”
Section: Inhibitors Of Chromosome Instability In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplication of the single G 1 centrosome begins at the G 1 /S transition and is completed during S-phase, so that two centrosomes are present in G 2 . These facilitate bipolar spindle formation at metaphase and are then segregated, one into each daughter cell, during cytokinesis [ 53 , 54 ]. Key to centrosome replication is centriole duplication, as the pre-existing mother centriole duplicates itself to form a daughter centriole.…”
Section: The Centrosome Cyclementioning
confidence: 99%